The Role of Animal Source Foods in Improving Nutritional Health in Urban Informal Settlements: Identification of Knowledge Gaps and Implementation Barriers - James, Allison E.; Palmer, Guy H. (International Journal of Child Health and Nutrition, 2015)
Childhood undernutrition is a health crisis in the rapidly expanding informal settlements of low-income countries worldwide. Nearly half of Kenyan children in the Kibera settlement, in Nairobi, were reported to be stunted, indicating low height-for-age. Stunted children are at greater risk for poor cognitive and physical health outcomes in the long-term, problems that tend to be perpetuated in subsequent generations. Animal-source foods (ASF) supply a calorically dense source of micro- and macronutrients, and supplementation with ASF has been shown to improve linear growth and cognition. Correspondingly, increasing consumption of ASF by pregnant women and children has been proposed as a means to disrupt the intergenerational cycle of undernutrition caused by food insecurity. Household surveys indicate that consumption of ASF is low in urban slums, despite the availability of these foods in local markets. Here we review the studies addressing the role of ASF in the diets of the urban poor and identify knowledge gaps relevant to improving nutrition by increasing consumption of ASF. Based predominantly on studies in Kibera and greater Nairobi, these gaps include determining the minimal amount and frequency of dietary ASF to prevent stunting, defining how consumer preferences, markets, and income interact to impede or promote ASF consumption, and understanding the interaction between diet and both clinical and sub-clinical enteric disease on growth outcomes.